How do open data enhances public accountability? : An analysis of the Metropolitan District of Quito open government portal (2014-2019) (Ágora de Heterodoxias, 2023)
Open government data portals have been embraced for their ability to improve transparency and strengthen democratic control. However, previous studies suggest that this relationship is complex and is conditioned by the portal's design itself and its proper use by interested users. This article analyzes the relationship between open data and democratic control through an analysis of the design and uses of the open government portal of the Metropolitan District of Quito. The structure, organization and presentation of the information is assessed and its online uses are tracked. Evidence indicates that, although some good practices are applied, there are many shortcomings in the portal design and very limited use of the data offered to assess government management.
Keywords: Open Data; Municipal Government; Government Control